Design and Construct of Magnetic Induction and Force Practicum Tools to Improve Science Process Skills - Muhammad Basir; Andhy Setiawan; Didi Teguh Chandra (Postgraduate, University of Mataram, 2024)
The purpose of this study was to design and construct magnetic induction and force practicum tools (AlPrIGMa) to improve science process skills. This research belongs to Research and Development (R&D) research using the Hannafin & Peck development model which consists of three main stages, namely need assessment, design, as well as development and implementation. The research instruments used in this research include expert validation sheets, student response sheets, science process skills observation sheets, and science process skills test questions. The results of the assessment undertaken by 3 experts showed a percentage of tool feasibility of 89.3% with a very feasible category. In addition, the response from 10 students after testing the tools obtained an average percentage of 83% in the very good category. The results of the application of the tools showed that there was an increase in each aspect of science process skills with an average N-gain score of 0.71 in the high category. Based on the effectiveness test, the independent t result is 0.009 < alpha value (0.05), which shows that AlPrIGMa is proven effective in improving science process skills.